Measurement of foot bone mineral density by dual energy X-ray absorptiometry in patients with rheumatoid arthritis and normal volunteers: Development of the method, its application and clinical relevance - Kamanli, A; Ozgocmen, S; Ardicoglu, O; Suluhan, O; Ciftci, I (Springer London Ltd, 2004)
[Abstract Not Available]
IOF World Congress on Osteoporosis -- MAY 14-18, 2004 -- Rio de Janeiro, BRAZIL